2020
DOI: 10.1155/2020/8895003
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Long Noncoding RNA LUCAT1 Inhibits High-Glucose-Induced Epithelial-Mesenchymal Transition through the miR-199a-5p–ZEB1 Axis in Human Renal Tubular Epithelial Cells

Abstract: Renal fibrosis, the leading cause of end-stage renal disease and in which epithelial-mesenchymal transition (EMT) plays a central role, has a complex pathogenesis that is not fully understood. Therefore, we investigated the role of the long noncoding RNA LUCAT1 in the EMT of renal tubular epithelial cells under high-glucose (HG) conditions and the underlying mechanism involved. In this study, we established HG and normal glucose groups of HK-2 cells by treating HK-2 cells 30.0 or 5.5 mmol/L glucose, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This study proved that high glucose conditions could enhance the ability of migration and invasion in LUAC cells. Lin and colleagues found that LUCAT1 was upregulated under high-glucose conditions, and knockdown of LUCAT1 inhibited the EMT in HG-treated HK-2 cells (Zhang et al, 2020). Therefore, we assumed that LUCAT1 might regulate migration and invasion of LUAD cells by participating in the process of glucose metabolism.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study proved that high glucose conditions could enhance the ability of migration and invasion in LUAC cells. Lin and colleagues found that LUCAT1 was upregulated under high-glucose conditions, and knockdown of LUCAT1 inhibited the EMT in HG-treated HK-2 cells (Zhang et al, 2020). Therefore, we assumed that LUCAT1 might regulate migration and invasion of LUAD cells by participating in the process of glucose metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, growing evidence have provided for cancer cells' dependent on glycolysis for energy production (Vander Heiden et al, 2009). It was reported that LUCAT1 was upregulated under high-glucose conditions, and knockdown of LUCAT1 inhibited the EMT in HG-treated HK-2 cells (Zhang et al, 2020), however, whether LUCAT1 participate in glycolysis of LUAD cells needs to be confirmed.…”
Section: Lung Cancer-associated Transcript 1 Regulated Lung Adenocarc...mentioning
confidence: 98%
“…The authors demonstrated modulation of EMT genes and stem cancer markers and suspect that miR-199a-5p may be involved in chemotherapy sensitivity in TNBC [ 146 ]. Further, through targeting ZEB1, miR-199a-5p inhibits EMT of ovarian ectopic endometrial stromal cells via the PI3K/Akt/mTOR signal pathway and in human renal tubular epithelial cells [ 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that miR‐199a‐5p and DDR1 axis also play important roles in glioma progression. Other mRNAs have also been identified as the targets of miR‐199a‐5p, including NRP1 in sepsis, 31 Klotho in gastric cancer, 32 and ZEB1 in human renal tubular epithelial cells 33 . Further experiments should be performed to investigate the regulatory axis of miR‐199a‐5p and these potential mRNA targets in glioma.…”
Section: Discussionmentioning
confidence: 99%